Optimization of a microplate-based assay to assess esterase activity in the alga Pseudokirchneriella subcapitata - Machado, Manuela D. (2013)
The present work describes the optimization of a short-term assay, based on the inhibition of the esterase activity of the alga Pseudokirchneriella subcapitata, in a microplate format. The optimization of the staining procedure showed that the incubation of the algal cells with 20 μmol L−1 fluorescein diacetate (FDA) for 40 min allowed discrimination between metabolic active and inactive cells. The short-term assay was tested using Cu as toxicant. For this purpose, algal cells, in the exponential or stationary phase of growth, were exposed to the heavy metal in growing conditions. After 3 or 6 h, cells were subsequently stained with FDA, using the optimized procedure. For Cu, the 3- and 6-h EC50 values, based on the inhibition of the esterase activity of algal cells in the exponential phase of growth, were 209 and 130 μg L−1, respectively. P. subcapitata cells, in the stationary phase of growth, displayed higher effective concentration values than those observed in the exponential phase. The 3- and 6-h EC50 values for Cu, for cells in the stationary phase, were 443 and 268 μg L−1, respectively. This short-term microplate assay showed to be a rapid endpoint for testing toxicity using the alga P. subcapitata. The small volume required, the simplicity of the assay (no washing steps), and the automatic reading of the fluorescence make the assay particularly well suited for the evaluation of the toxicity of a high number of environmental samples.